Adipose tissue macrophages in remote modulation of hepatic glucose production - Tao, Yan; Jiang, Quanhong; Wang, Qun (Frontiers in Immunology, 2022)
Hepatic glucose production (HGP) is fine-regulated via glycogenolysis or gluconeogenesis to maintain physiological concentration of blood glucose during fasting-feeding cycle. Aberrant HGP leads to hyperglycemia in obesity-associated diabetes. Adipose tissue cooperates with the liver to regulate glycolipid metabolism. During these processes, adipose tissue macrophages (ATMs) change their profiles with various physio-pathological settings, producing diverse effects on HGP. Here, we briefly review the distinct phenotypes of ATMs under different nutrition states including feeding, fasting or overnutrition, and detail their effects on HGP. We discuss several pathways by which ATMs regulate hepatic gluconeogenesis or glycogenolysis, leading to favorable or unfavorable metabolic consequences. Furthermore, we summarize emerging therapeutic targets to correct metabolic disorders in morbid obesity or diabetes based on ATM-HGP axis. This review puts forward the importance and flexibility of ATMs in regulating HGP, proposing ATM-based HGP modulation as a potential therapeutic approach for obesity-associated metabolic dysfunction.